2017
DOI: 10.1002/uog.17484
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell‐free DNA in maternal blood in screening for aneuploidies: updated meta‐analysis

Abstract: Objectives To review clinical validation or implementation studies of maternal blood cell-free (cf) DNA analysis and define the performance of screening for fetal trisomies 21, 18 and 13 and sex chromosome aneuploidies (SCA). Methods Searches of PubMed, EMBASE and The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
572
4
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(618 citation statements)
references
References 45 publications
28
572
4
14
Order By: Relevance
“…Two cases of trisomy 21 and one case of Cridu-chat syndrome were confirmed by amniocentesis, whereas one case of 46,XN,del(16q11.2-q22.3) and another case of 46,XN,dup(Xp22.31) were considered as normal. Previous studies have reported that NIPT could be successfully validated for common aneuploidies in singleton pregnancies; and the detection rates were 99.7% for trisomy 21, 98% for trisomy 18, and 99% for trisomy 13 with a combined false-positive rate (FPR) of 0.13% (10), and the detection rate for subchromosome abnormalities was 71.8% (11). Another study using NIPT to identify common aneuploidies reported that the sensitivity and specificity were 99.94% and 99.46% for trisomy 21, 100% and 99.24% for trisomy 18, and 100% and 100% for trisomy 13, respectively (12).…”
Section: Discussionmentioning
confidence: 99%
“…Two cases of trisomy 21 and one case of Cridu-chat syndrome were confirmed by amniocentesis, whereas one case of 46,XN,del(16q11.2-q22.3) and another case of 46,XN,dup(Xp22.31) were considered as normal. Previous studies have reported that NIPT could be successfully validated for common aneuploidies in singleton pregnancies; and the detection rates were 99.7% for trisomy 21, 98% for trisomy 18, and 99% for trisomy 13 with a combined false-positive rate (FPR) of 0.13% (10), and the detection rate for subchromosome abnormalities was 71.8% (11). Another study using NIPT to identify common aneuploidies reported that the sensitivity and specificity were 99.94% and 99.46% for trisomy 21, 100% and 99.24% for trisomy 18, and 100% and 100% for trisomy 13, respectively (12).…”
Section: Discussionmentioning
confidence: 99%
“…Using FTCS, the detection and false-positive rates for trisomy 21 are about 90-95% and 2.5-5%, respectively. In contrast, these rates improve to 99 and 0.1% using cfDNA screening [7]. However, due to concerns about the potential cost of implementing universal cfDNA screening, many groups advocate a contingent approach.…”
mentioning
confidence: 90%
“…In a recent meta-analysis, Gil et al [7] summarized the test performance of cfDNA screening for trisomy 21. The updated detection and false-positive rates were 99.7 and 0.04%, respectively.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Among these metrics, measurement of the fetal fraction (FF) of DNA found in maternal plasma is considered to be important, since a low FF can potentially lead to a higher likelihood of a falsenegative result [12][13][14]. Several factors associated with uninformative cfDNA results or a low FF have been identified, such as maternal weight, a low level of pregnancyassociated plasma protein A, twin pregnancy, and conception by in vitro fertilization (IVF) [15,16]. So far, 3 approaches for the analysis of cfDNA in maternal blood have been used in clinical studies: genome-wide massively parallel sequencing (GW-MPS) and targeted (chromosome-selective) methods based on digital analysis of selected regions of polymorphic as well as nonpolymorphic loci by massively parallel sequencing or array technology (DANSR TM ) or based on assessment of single nucleotide polymorphisms (SNPs) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2011, cfDNA testing has been commercially available for screening for trisomies, and increasing evidence suggests that analysis of cfDNA in maternal blood can detect about 99.7% of cases of trisomy 21,97.9% of cases of trisomy 18, and 99.0% of cases of trisomy 13 at a combined FPR of 0.13% [4]. Such high-performance screening has been reported for both high-risk pregnancies and in the general population [4][5][6][7][8][9]. Beyond the major trisomies (21,18, and 13), cfDNA testing panels can be expanded to include sex chromosomal aneuploidies and microdeletion syndromes, but this would increase the cumulative FPR [10].…”
Section: Introductionmentioning
confidence: 99%